Preliminary evaluation of the sensitivity to change of DE-STA motor unit number estimation in the upper trapezius muscle in amyotrophic lateral sclerosis - Ives, Colleen T.; Findlater, Karen; Shoesmith, Christen L.; Doherty, Timothy J. (Clinical neurophysiology, 2015)
•Decomposition-enhanced spike-triggered averaging (DE-STA) motor unit number estimation (MUNE) demonstrated a moderate degree of sensitivity to change in subjects with amyotrophic lateral sclerosis (ALS).•Variability in the results of DE-STA MUNE between time points indicates a need for future investigation regarding potential sources of error associated with the technique.•This study has established the feasibility of the longitudinal application of DE-STA MUNE to the upper trapezius muscle in ALS. To compare the sensitivity to change of decomposition-enhanced spike-triggered averaging (DE-STA) motor unit number estimation (MUNE) in the upper trapezius (UT) to that of various clinical outcome measures in subjects with amyotrophic lateral sclerosis (ALS). Ten patients with clinically probable or definite ALS were assessed at baseline, 2, 4 and 6months with the following outcome measures: manual muscle testing in five upper extremity muscle groups, scapular elevation and elbow flexion peak force measured with hand-held dynamometry, MUNE, forced vital capacity and the Revised ALS Functional Rating Scale (ALSFRS-R). ALSFRS-R was the only outcome measure for which there was a significant difference between baseline and 6months (p=0.034). ALSFRS-R had the largest standardized response mean (SRM), and was thus the most sensitive to change. MUNE demonstrated a decline over 6months and a moderate SRM (−0.63). This study has demonstrated a moderate degree of sensitivity to change for DE-STA MUNE as applied to the UT in subjects with ALS. In this preliminary study, DE-STA MUNE detected motor unit loss over 6months, with a moderate degree of sensitivity, in the upper trapezius of subjects with ALS.